Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
By physically mixing lithium iron phosphate and LiMnxFe1-xPO4 and sintering, the problem of difficult to prepare lithium iron phosphate positive electrode materials with excellent electrochemical performance in the prior art is solved, and the effect of simplifying the process, reducing costs and improving battery performance is achieved.
Patent Information
- Application Number
- CN202311130225.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-04
AI Technical Summary
It is difficult to effectively use waste lithium iron phosphate batteries to prepare lithium iron phosphate positive electrode materials with excellent electrochemical performance, and the preparation method of lithium iron phosphate is complex and costly.
By physically mixing lithium iron phosphate and LiMnxFe1-xPO4 and sintering, a lithium iron phosphate positive electrode material with stable crystalline shape and uniform particle size is prepared, which avoids the chemical reagent synthesis process, simplifies the process and reduces costs.
The lithium manganese iron phosphate positive electrode material with excellent electrochemical performance has been prepared, which improves the circulation performance and charge and discharge capacity of lithium batteries, and is simple in process and low in cost, which is suitable for industrial applications.
Smart Images

Figure CN119551642A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present invention relate to the field of battery technology, and in particular to a lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of new energy vehicles in my country, a large number of lithium-ion power batteries have been applied to new energy vehicles. The life cycle of lithium-ion power batteries is generally 5-8 years, and some are even shorter. The development of new energy vehicles has a history of nearly 10 years. Therefore, with the passage of time, a large number of waste lithium-ion power batteries are generated, and most of them are lithium iron phosphate power batteries and lithium manganese oxide power batteries. For such a large number of waste power batteries, the current common practice is to re-assemble the waste power batteries and apply them to the energy storage field. This method can dispose of a large number of waste lithium-ion power batteries in a short time. However, people also realize that this is only a temporary treatment method. The performance of lithium-ion batteries will eventually decay to the point where they can no longer be used. Therefore, there are also many battery companies or battery recycling companies that are engaged in the recycling and regeneration technology of waste lithium-ion power batteries.
[0003] The prior art mentions that waste lithium iron phosphate batteries are used to regenerate lithium iron phosphate cathode materials through a series of means, but their electrochemical performance is not as good as that of the first synthesized lithium iron phosphate. There are also reports that lithium iron phosphate is resynthesized by acid hydrolysis, and the performance of the lithium iron phosphate material synthesized by this method is basically the same as that of the first synthesized lithium iron phosphate. However, in the development direction of high energy density of lithium-ion power batteries, lithium iron phosphate batteries are almost approaching a bottleneck. Seeking a high energy density electrochemical system has become a consensus in the industry. Lithium iron manganese phosphate has the same crystal structure as lithium iron phosphate, but the energy density of lithium iron manganese phosphate is much higher than that of lithium iron phosphate, and the content of each element of lithium iron manganese phosphate is rich and environmentally friendly. It is considered to be the next generation material system to replace lithium iron phosphate materials. However, the current preparation methods of lithium iron manganese phosphate all use high-purity chemical reagents for synthesis, which is complex and costly. Summary of the invention
[0004] The technical problem solved by the embodiments of the present invention is how to use lithium iron phosphate to prepare lithium manganese iron phosphate positive electrode material with excellent electrochemical performance.
[0005] In order to solve the above problems, an embodiment of the present invention provides a method for preparing a lithium manganese iron phosphate positive electrode material, comprising:
[0006] Available in LiFePO4 and LiMn x Fe 1-x PO4, x>0.5;
[0007] The lithium iron phosphate and the LiMn x Fe 1-xPO4 is physically mixed and then sintered to obtain the lithium manganese iron phosphate positive electrode material.
[0008] Optionally, the sintering temperature ranges from 450°C to 750°C.
[0009] Optionally, the sintering heating rate ranges from 1°C / min to 20°C / min, and the cooling rate ranges from 1°C / min to 20°C / min.
[0010] Optionally, the LiMn x Fe 1-x PO4 before physical mixing, also includes the LiMnxFe 1-x PO4 is treated with carbon coating.
[0011] Optionally, the lithium iron phosphate and the LiMn x Fe 1-x The steps of physical mixing of PO4 include: mixing LiMnxFe 1- x PO4 and LiFePO4 are ground at room temperature until there is no obvious particle feeling.
[0012] Optionally, the specific steps of the carbon coating treatment include: x Fe 1-x PO4 and carbon source were ground and mixed, and sintered in a nitrogen atmosphere. The sintering conditions were: kept at 200°C for 2 hours, then heated to 450°C for 2 hours, and finally heated to 700°C for 5 hours, with a heating rate of 2°C / min and a cooling rate of 1°C / min.
[0013] Optionally, LiMn x Fe 1-x Before the PO4 and the carbon source are ground and mixed, the process also includes: adding alcohol to the mixture, wherein the content of the alcohol is in the range of 40%-60%.
[0014] Optionally, the carbon source includes at least one of glucose, sucrose, polyethylene glycol, and polyvinyl alcohol.
[0015] Optionally, the carbon source has a content percentage ranging from 2wt% to 20wt%.
[0016] Optionally, the ratio of manganese element to iron element in the lithium manganese iron phosphate positive electrode material is 1:1.
[0017] Optionally, the specific surface area of the lithium manganese iron phosphate cathode material is approximately 21-34m 2 / g; the average particle size range is 170-280nm.
[0018] In order to solve the above problems, an embodiment of the present invention provides a lithium iron manganese phosphate positive electrode material, which is obtained by the above preparation method.
[0019] In order to solve the above problems, an embodiment of the present invention provides an application of the above lithium iron manganese phosphate positive electrode material in a positive electrode material of a lithium battery.
[0020] Compared with the prior art, the technical solution of the embodiment of the present invention has the following advantages:
[0021] The present invention provides a method for preparing a lithium iron manganese phosphate positive electrode material, using LiFePO4 and LiMn x Fe 1- x PO4 is used as the two reaction raw materials of the "model reaction". Lithium iron phosphate and LiMn x Fe 1-x PO4 mixed sintering, this solid phase reaction process can prepare a lithium iron manganese phosphate positive electrode material with stable crystal form and uniform particle size, and improve the cycle performance and charge and discharge capacity of the battery. It can be seen that the preparation method of the lithium iron manganese phosphate positive electrode material provided in the embodiment of the present invention, on the one hand, only needs two raw materials to be simply mixed and sintered at a certain temperature to obtain a lithium iron manganese phosphate positive electrode material with stable crystal form and uniform particle size, avoiding the chemical reagent synthesis process, not only saving costs, but also simple operation, strong industrial applicability; on the other hand, it can be used to recycle LiFePO4 materials, and by recycling and reusing lithium iron phosphate, the added value of lithium iron phosphate can be increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0023] Figure 1 This is a flow chart of a method for preparing a lithium iron manganese phosphate positive electrode material provided by an embodiment of the present invention;
[0024] Figure 2 The samples 1-7 in Example 1 of the present invention, the raw materials LiFePO4, LiMn 0.7 Fe 0.3 XRD patterns of PO4 and physical mixture of raw materials (Mixed-25℃);
[0025] Figure 3 The sample 6 in Example 1 of the present invention, the raw materials LiFePO4, LiMn 0.7 Fe 0.3 Electron microscope images of PO4 and raw material physical mixture (Mixed-25℃);
[0026] Figure 4 It is the EDS spectrum analysis diagram of Mixed-25℃ and S-700℃ (sample 6) in Example 1 of the present invention;
[0027] Figure 5 is a comparison chart of the specific surface areas of the raw materials and various samples in Example 1 of the present invention;
[0028] Figure 6 is a comparison diagram of the particle sizes of the raw materials and samples in Example 1 of the present invention;
[0029] Figure 7-Figure 8 It is a comparison chart of the electrochemical performance of the batteries of Examples 2-4 of the present invention and Comparative Example 2. DETAILED DESCRIPTION
[0030] As can be seen from the background technology, the current preparation methods of lithium manganese iron phosphate all use high-purity chemical reagents for synthesis, which has complex processes and high costs.
[0031] like Figure 1 As shown, in order to solve the above problems, an embodiment of the present invention provides a method for preparing a lithium manganese iron phosphate positive electrode material, comprising:
[0032] S1, provides lithium iron phosphate and LiMn x Fe 1-x PO4, x>0.5;
[0033] The conductivity of the battery with lithium iron phosphate (LiFePO4) as the active material is poor. By using LiFePO4 as a raw material to prepare lithium iron manganese phosphate materials with better conductivity, it is possible to recycle LiFePO4, improve resource utilization, and increase the energy density of the battery. On the other hand, lithium iron phosphate (LiFePO4) can provide both lithium and iron elements. x Fe 1-x No additional lithium or iron source is required during the PO4 modification process, and the process is simple.
[0034] Raw materialLiMn x Fe 1-x The element ratio of Mn to Fe in PO4 should be greater than 1, that is, x>0.5, further, x≥0.6, and more preferably, x≥0.7. The larger the proportion of Mn, the more unfavorable it is for LiMn x Fe 1-x PO4 plays its chemical properties as a battery active material. Therefore, in order to rationally utilize resources, in one embodiment, the raw material LiMn x Fe 1-x PO4 is LiMn 0.7 Fe 0.3PO4. By using two raw materials with poor chemical properties, a lithium iron manganese phosphate material with excellent chemical properties is prepared. Of course, in other embodiments, the raw material LiMn x Fe 1-x PO4 can also be LiMn 0.6 Fe 0.4 PO4, LiMn 0.8 Fe 0.2 PO4, LiMn 0.9 Fe 0.1 PO4, etc., as long as the value of x is greater than or equal to 0.6.
[0035] By regulating the lithium iron phosphate and raw material LiMn x Fe 1-x The molar ratio of PO4 is used to adjust the ratio of Mn and Fe in the final synthesized lithium manganese iron phosphate. x Fe 1-x The molar percentage range of PO4 is related to the proportion of Mn and Fe elements in the final desired lithium manganese iron phosphate positive electrode material.
[0036] S2, the lithium iron phosphate and the LiMn x Fe 1-x PO4 is physically mixed and then sintered to obtain the lithium manganese iron phosphate positive electrode material.
[0037] By combining lithium iron phosphate and the LiMn x Fe 1-x PO4 is mixed and sintered, and LiMn with a relatively large proportion of Mn element x Fe 1-x PO4 and LiFePO4 are fused together during the sintering process to obtain a lithium manganese iron phosphate positive electrode material with a reduced proportion of Mn element. The lithium manganese iron phosphate positive electrode material has a stable crystal form and uniform particle size, avoids the chemical reagent synthesis process, not only saves costs, but also is simple to operate and has strong industrial applicability.
[0038] It should be noted that by adjusting the raw materials lithium iron phosphate and LiMnxFe 1-x PO4 molar ratio, can produce manganese iron phosphate lithium positive electrode materials with different proportions of manganese and iron. For example, after mixing and sintering the two raw materials, the ratio of manganese and iron in the manganese iron phosphate lithium positive electrode material is 1:1, and the molecular formula is LiMn 0.5 Fe 0.5 Of course, in other embodiments, the ratio of manganese to iron in the final prepared lithium manganese iron phosphate positive electrode material does not exceed that of the raw material LiMn x Fe 1-xThe ratio of manganese to iron in PO4 is sufficient. For example, when x = 0.7 (LiMn 0.7 Fe 0.3 PO4), the ratio of Mn and Fe elements in the finally prepared lithium manganese iron phosphate positive electrode material can be (6-1):(4-9), such as 3:2, 2:3, 3:7, 1:4 or 1:9.
[0039] The sintering temperature range should not be too high or too low. If the sintering temperature is too high, impurities may be produced. Too high a temperature is not conducive to the realization of lithium iron phosphate and LiMn x Fe 1-x Fusion of PO4; if the sintering temperature is too low, the reaction may not be complete. Therefore, in a specific embodiment, in order to effectively ensure the purity of the sintered material and avoid the generation of impurities, the sintering temperature can range from 450°C to 750°C, further, 600°C to 750°C, and further, it can be 600°C to 700°C.
[0040] The heating rate of sintering is in the range of 1°C / min-20°C / min. Further, it can be 1°C / min-10°C / min, 2°C / min-5°C / min.
[0041] The cooling rate range is 1°C / min-20°C / min. Further, it can be 1°C / min-10°C / min, 1°C / min-5°C / min.
[0042] In step S2, the LiMn x Fe 1-x Before physical mixing with PO4, step S3 is also included to treat the LiMnxFe 1- x PO4 is carbon coated to protect the surface of LiMnFePO4 from being corroded by the electrolyte.
[0043] The lithium iron phosphate and the LiMnxFe 1-x The steps of physical mixing of PO4 include: x Fe 1-x PO4 and LiFePO4 are ground at room temperature until there is no obvious particle feeling.
[0044] The specific steps of the carbon coating treatment include: x Fe 1-x PO4 and carbon source were ground and mixed, and sintered in a nitrogen atmosphere. The sintering conditions were: 200°C for 2 hours, then heated to 450°C for 2 hours, and finally heated to 700°C for 5 hours, with a heating rate of 2°C / min and a cooling rate of 1°C / min.
[0045] In order to facilitate uniform mixing and grinding, LiMnxFe 1-x Before the PO4 and the carbon source are ground and mixed, the process also includes: adding alcohol to the mixture, wherein the content of the alcohol is in the range of 40%-60%.
[0046] The carbon source may include at least one of glucose, sucrose, polyethylene glycol, and polyvinyl alcohol.
[0047] The percentage content of the carbon source ranges from 2wt% to 20wt%, such as 5wt%, 10wt%, and 15wt%.
[0048] Among them, the specific surface area of lithium manganese iron phosphate positive electrode material is about 21-34m 2 / g; the average particle size range is 170-280nm.
[0049] The method for preparing the lithium manganese iron phosphate positive electrode material provided in the embodiment of the present invention is to use LiFePO4 and LiMn x Fe 1- x PO4 is used as the two reaction raw materials of the "model reaction". Lithium iron phosphate and LiMn x Fe 1-x PO4 mixed sintering, this solid phase reaction process can prepare a lithium iron manganese phosphate positive electrode material with stable crystal form and uniform particle size, and improve the cycle performance and charge and discharge capacity of the battery. It can be seen that the preparation method of lithium iron manganese phosphate provided in the embodiment of the present invention, on the one hand, only requires two raw materials to be simply mixed and sintered at a certain temperature to obtain a lithium iron manganese phosphate positive electrode material with stable crystal form and uniform particle size, avoiding the chemical reagent synthesis process, not only saving costs, but also simple operation, and strong industrial applicability; on the other hand, it can be used to recycle LiFePO4 materials, and by recycling and reusing lithium iron phosphate, the added value of lithium iron phosphate can be increased.
[0050] In order to solve the above problems, an embodiment of the present invention further provides a lithium iron manganese phosphate positive electrode material, and the lithium iron manganese phosphate positive electrode material can be obtained by the above preparation method.
[0051] By combining lithium iron phosphate and LiMn x Fe 1-x PO4 mixed sintering, this solid phase reaction process can prepare lithium manganese iron phosphate positive electrode material with stable crystal form and uniform particle size, thereby improving the cycle performance and charge and discharge capacity of lithium batteries.
[0052] In order to solve the above problems, an embodiment of the present invention provides an application of a lithium iron manganese phosphate positive electrode material in a positive electrode material of a lithium battery.
[0053] Specifically, an embodiment of the present invention provides a positive electrode sheet, using the above-mentioned lithium iron manganese phosphate positive electrode material as an active material. An embodiment of the present invention also provides a lithium ion battery, the lithium ion battery comprising the above-mentioned positive electrode sheet.
[0054] By combining lithium iron phosphate and LiMn x Fe 1-x PO4 mixed sintering, this solid phase reaction process can prepare lithium manganese iron phosphate positive electrode material with stable crystal form and uniform particle size, thereby improving the battery's cycle performance and charge and discharge capacity.
[0055] The lithium manganese iron phosphate positive electrode material and the preparation method and battery of the present invention are further described in detail below in combination with specific examples and comparative examples.
[0056] Example 1
[0057] Step 1, LiMn 0.7 Fe 0.3 PO4 is treated with carbon: LiMn 0.7 Fe 0.3 PO4 was ground and mixed with 5wt% sucrose, and sintered in a nitrogen atmosphere. The sintering conditions were: 200℃, 2h; 450℃, 2h; 700℃, 5h, heating rate 2℃ / min, cooling rate 1℃ / min;
[0058] Step 2: LiFePO4 (LFP) and carbon-coated LiMn 0.7 Fe 0.3 PO4(LiMn 0.7 Fe 0.3 PO4@C) were physically mixed at room temperature in a molar ratio of 7:18 (referred as Mixed-25°C), alcohol (solid content of about 50%) was added, and the mixture was ground at room temperature until no obvious particles were felt (ball milling speed of 400 rpm, 6 h), and then dried with forced air (80°C, 12 h);
[0059] Step 3, mixed sintering: The mixed powder obtained in step 2 is placed in a tube furnace for sintering, mixed sintering under N2 atmosphere, heating rate 2℃ / min, cooling rate 1℃ / min, to obtain lithium manganese iron phosphate positive electrode material, the chemical formula is LiMn 0.5 Fe 0.5 PO4, where the sintering procedure corresponds to the following:
[0060] 200℃, 2h; 450℃, 2h, to obtain sample 1 (denoted as S-450℃);
[0061] 200℃, 2h; 450℃, 2h; 500℃, 5h, to obtain sample 2 (denoted as S-500℃);
[0062] 200℃, 2h; 450℃, 2h; 550℃, 5h, to obtain sample 3 (denoted as S-550℃);
[0063] 200℃, 2h; 450℃, 2h; 600℃, 5h, to obtain sample 4 (denoted as S-600℃);
[0064] 200℃, 2h; 450℃, 2h; 650℃, 5h, to obtain sample 5 (denoted as S-650℃);
[0065] 200℃, 2h; 450℃, 2h; 700℃, 5h, to obtain sample 6 (denoted as S-700℃);
[0066] 200℃, 2h; 450℃, 2h; 750℃, 5h, and sample 7 (denoted as S-750℃) was obtained.
[0067] Samples 1-7, raw materials LiFePO4 (LFP), LiMn 0.7 Fe 0.3 PO4(MF73) and LiFePO4, LiMn 0.7 Fe 0.3 After PO4 physical mixing (Mixed-25℃), XRD test was performed, and the results were as follows Figure 2 shown.
[0068] Depend on Figure 2 It can be seen that at room temperature, physical mixing Mixed-25℃ shows both diffraction peaks of LiFePO4 and LiMn 0.7 Fe 0.3 Diffraction peak of PO4. By mixing the samples and sintering them, as the temperature increases (from 450℃ to 750℃), the two diffraction peaks gradually become one, and the half-peak width gradually decreases, indicating that as the sintering temperature increases, the crystallinity of the samples becomes better and better.
[0069] The electron microscope morphology analysis of sample 6 showed the following results: Figure 3 As shown. Among them, Figure a shows that LiFePO4 is a large particle, and Figure b shows that LiMn 0.7 Fe 0.3 PO4 is a small particle, and Figure c is a mixture of LiFePO4 and LiMn 0.7 Fe 0.3 PO4 mixed at room temperature (Mixed-25℃), LiFePO4 large particles and LiMn 0.7 Fe 0.3 Figure d is sample 6 (S-700℃): After sintering at 700℃, many large LiFePO4 particles disappeared, and most of them retained LiMn 0.7 Fe 0.3The morphology of PO4 small particles.
[0070] EDS spectrum analysis was performed on Mixed-25℃ and S-700℃ respectively. The test results are as follows: Figure 4 As shown. It can be seen that for the sample Mixed-25℃: large particles of LiFePO4 and small particles of LiMn 0.7 Fe 0.3 PO4 exists in large quantities; Mn and Fe are enriched in different areas; LiMn 0.7 Fe 0.3 PO4 and LiFePO4 are distributed separately.
[0071] For sample 6 (S-700℃): compared with the sample Mixed-25℃, the small particles of LiMn 0.7 Fe 0.3 PO4 accounts for a larger proportion, and large particles of LiFePO4 disappear a lot; Mn and Fe are enriched in the same area; LiMn 0.7 Fe 0.3 PO4 and LiFePO4 are fused together during the sintering process, indicating that the preparation method of lithium manganese iron phosphate provided by the embodiment of the present invention only requires two raw materials to be simply mixed and sintered at a certain temperature to obtain a lithium manganese iron phosphate positive electrode material with stable crystal form and uniform particle size.
[0072] The specific surface area and particle size of samples 1-7 were tested by BET specific surface area detection method (instrument model F-Sorb X400). The test results are as follows: Figure 5 and Figure 6 shown.
[0073] Combination Figure 5 and Figure 6 It can be seen that as the heating temperature increases, the specific surface area of the lithium manganese iron phosphate positive electrode material gradually decreases and the particle size gradually increases. Combined with the analysis of XRD and SEM, the LiFePO4 particles gradually disappear, and LiFePO4 fuses into LiMn 0.7 Fe 0.3 PO4. The specific surface area of the sintered lithium manganese iron phosphate positive electrode material is about 21-34m 2 / g; the average particle size range is 170-280nm.
[0074] Example 2
[0075] Pole piece preparation: Sample 5 (S-650℃) (93wt%) in Example 1, conductive additives conductive carbon black SuperP (2wt%) and conductive graphite KS-6 (2wt%), and binder PVDF solution (3wt%) were mixed evenly, and then the mixed slurry was evenly coated on a clean aluminum foil with a scraper, with a coating thickness of 250μm, and placed in a vacuum transition chamber at 80℃ to dry for 8h. The battery active material loading was about 10mg / cm 2 , rolled with an electric double-roller press, the rolled bottom thickness is about 1.1 mm, and then pressed with a tablet press to prepare an electrode sheet with a diameter of 12 mm.
[0076] Button battery assembly
[0077] The reaction was carried out in a glove box (MBRAUN LABMASTER 130) under Ar atmosphere protection. The electrolyte was 1M LiPF6 (EC / DMC / EMC=1:1:1), 2% VC was used as an additive, the separator was a Celgard-2500 polypropylene microfilm, the electrode sheet of Example 2 was used as the working electrode, and the counter electrode was a fresh lithium sheet.
[0078] Conduct relevant performance tests on button batteries.
[0079] Example 3
[0080] Pole piece preparation: Sample 6 (S-700℃) (93wt%) in Example 1, conductive additives conductive carbon black SuperP (2wt%) and conductive graphite KS-6 (2wt%), and binder PVDF solution (3wt%) were mixed evenly, and then the mixed slurry was evenly coated on a clean aluminum foil with a scraper, with a coating thickness of 250μm, and placed in a vacuum transition chamber at 80℃ to dry for 8h. The battery active material loading was about 10mg / cm 2 , rolled with an electric double-roller press, the rolled bottom thickness is about 1.1 mm, and then pressed with a tablet press to prepare an electrode sheet with a diameter of 12 mm.
[0081] Button battery assembly
[0082] The reaction was carried out in a glove box (MBRAUN LABMASTER 130) under Ar atmosphere protection. The electrolyte was 1M LiPF6 (EC / DMC / EMC=1:1:1), 2% VC was used as an additive, the diaphragm was a Celgard-2500 polypropylene microfilm, the electrode sheet of Example 3 was used as the working electrode, and the counter electrode was a fresh lithium sheet.
[0083] Conduct relevant performance tests on button batteries.
[0084] Example 4
[0085] Pole piece preparation: Sample 7 (S-750℃) (93wt%) in Example 1, conductive additives conductive carbon black SuperP (2wt%) and conductive graphite KS-6 (2wt%), and binder PVDF solution (3wt%) were mixed evenly, and then the mixed slurry was evenly coated on a clean aluminum foil with a scraper, with a coating thickness of 250μm, and placed in a vacuum transition chamber at 80℃ to dry for 8h. The battery active material loading was about 10mg / cm 2 , rolled with an electric double-roller press, the rolled bottom thickness is about 1.1 mm, and then pressed with a tablet press to prepare an electrode sheet with a diameter of 12 mm.
[0086] Button battery assembly
[0087] The reaction was carried out in a glove box (MBRAUN LABMASTER 130) under Ar atmosphere protection. The electrolyte was 1M LiPF6 (EC / DMC / EMC=1:1:1), 2% VC was used as an additive, the separator was a Celgard-2500 polypropylene microfilm, the electrode sheet of Example 4 was used as the working electrode, and the counter electrode was a fresh lithium sheet.
[0088] Conduct relevant performance tests on button batteries.
[0089] Comparative Example 1
[0090] For LiMn 0.7 Fe 0.3 PO4 is treated with carbon: LiMn 0.7 Fe 0.3 PO4 was ground and mixed with 5wt% sucrose, and sintered in a nitrogen atmosphere. The sintering conditions were: 200℃, 2h; 450℃, 2h; 700℃, 5h, heating rate 2℃ / min, cooling rate 1℃ / min;
[0091] Step 2: LiFePO4 and carbon-coated LiMn 0.7 Fe 0.3 PO4(LiMn 0.7 Fe 0.3 PO4@C) were physically mixed at room temperature in a molar ratio of 7:18, alcohol (solid content of about 50%) was added, and the mixture was ground at room temperature until no obvious granularity was observed (ball mill speed of 400 rpm, 6 h), and then dried with forced air (80 °C, 12 h) to obtain a comparative sample (denoted as Mixed-25 °C).
[0092] The difference between Comparative Example 1 and Example 1 is that LiFePO4 and LiMn 0.7 Fe 0.3 PO4 was mixed but not sintered.
[0093] Comparative Example 2
[0094] Pole preparation: The comparative sample (Mixed-25℃) (93wt%), conductive additives conductive carbon black Super P (2wt%) and conductive graphite KS-6 (2wt%), and binder PVDF solution (3wt%) were mixed evenly, and then the mixed slurry was evenly coated on a clean aluminum foil with a scraper, with a coating thickness of 250μm, and placed in a vacuum transition chamber at 80℃ to dry for 8h. The battery active material loading was about 10mg / cm 2 , rolled with an electric double-roller press, the rolled bottom thickness is about 1.1 mm, and then pressed with a tablet press to prepare an electrode sheet with a diameter of 12 mm.
[0095] Button battery assembly
[0096] The reaction was carried out in a glove box (MBRAUN LABMASTER 130) under Ar atmosphere protection. The electrolyte was 1M LiPF6 (EC / DMC / EMC=1:1:1), 2% VC was used as an additive, the diaphragm was a Celgard-2500 polypropylene microfilm, the electrode sheet of Comparative Example 1 was used as the working electrode, and the counter electrode was a fresh lithium sheet.
[0097] Conduct relevant performance tests on button batteries.
[0098] All batteries in the experiment were charged and discharged on the Wuhan Blue Electric CT2001A battery testing system. The charging and discharging method is constant current charging and discharging, the LFP voltage range is 2.5~4.2V, and the LMFP (including the raw material MF73 and the final prepared lithium manganese iron phosphate positive electrode material) voltage range is 2.5~4.4V. The battery's specific capacity, cycle performance, rate performance, etc. are tested. The product of the charge and discharge rate and the theoretical specific capacity of the material is the theoretical charge and discharge current density at this rate. For LFP and LMFP materials, the theoretical specific capacity is 170mAh·g -1 For example, when discharging at 1C, the theoretical discharge current density is 170 mA g -1 , 0.1C is 17mA·g -1 , 2C is 340mA·g -1 The material cycle performance test in this paper is 0.1C activation for 2 cycles, and then 0.5C cycle for 300 cycles.
[0099] The electrochemical performance of Examples 2-4 and Comparative Example 2 is as follows Figure 7-8 As shown in Table 1-2.
[0100] Table 1 Charge and discharge capacity and first cycle coulombic efficiency of each material
[0101] <![CDATA[Charge specific capacity (mAh·g -1 )]]> <![CDATA[Discharge specific capacity (mAh·g -1 )]]> First cycle coulomb efficiency (%) <![CDATA[LiFePO4]]> 168.8 163.8 97.0 <![CDATA[LiMn 0.7 Fe 0.3 PO4]]> 156.5 145.4 92.9 Mixed-25℃ 161.8 153.3 94.7 S-650℃ 142.5 132.5 93.0 S-700℃ 148.2 142.4 96.1 S-750℃ 140.4 128.5 91.5
[0102] Table 2 Cyclic performance parameters of each substance
[0103]
[0104] Combination Figure 6 , Figure 7 As shown in Table 1 and Table 2, the lithium manganese iron phosphate positive electrode material prepared in the embodiment of the present invention has a capacity retention rate of more than 73.9% under long cycle, which significantly improves the capacity retention rate of the two raw materials. In particular, when the sintering temperature is 700°C, the capacity retention rate is as high as 91.2%, and the discharge specific capacity after 300 cycles is 114.3 mAh g -1 , indicating that the lithium manganese iron phosphate material prepared in the embodiment of the present invention can indeed improve the cycle performance of the lithium battery.
[0105] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0106] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: include: Available in LiFePO4 and LiMn x Fe 1-x PO4, x>0.5; The lithium iron phosphate and the LiMn x Fe 1-x PO4 is physically mixed and then sintered to obtain the lithium manganese iron phosphate positive electrode material.
2. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The sintering temperature ranges from 450°C to 750°C.
3. The method for preparing the lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The sintering heating rate range is 1℃ / min-20℃ / min, and the cooling rate range is 1℃ / min-20℃ / min.
4. The method for preparing the lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In the case of LiMn x Fe 1-x PO4 before physical mixing, including the LiMn x Fe 1-x PO4 is treated with carbon coating.
5. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The lithium iron phosphate and the LiMn x Fe 1-x The steps of physical mixing of PO4 include: x Fe 1-x PO4 and LiFePO4 are ground at room temperature until there is no obvious particle feeling.
6. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 4, characterized in that: The specific steps of the carbon coating treatment include: x Fe 1-x PO4 and carbon source were ground and mixed, and sintered in a nitrogen atmosphere. The sintering conditions were: kept at 200°C for 2 hours, then heated to 450°C for 2 hours, and finally heated to 700°C for 5 hours, with a heating rate of 2°C / min and a cooling rate of 1°C / min.
7. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 6, characterized in that: In LiMnxFe 1- x Before the PO4 and the carbon source are ground and mixed, the process also includes: adding alcohol to the mixture, wherein the content of the alcohol is in the range of 40%-60%.
8. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 6, characterized in that: The carbon source includes at least one of glucose, sucrose, polyethylene glycol, and polyvinyl alcohol.
9. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 6, characterized in that: The percentage content of the carbon source ranges from 2wt% to 20wt%.
10. The method for preparing the lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 9, characterized in that: The ratio of manganese to iron in the lithium manganese iron phosphate positive electrode material is 1:
1.
11. The method for preparing the lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 9, characterized in that: The specific surface area of the lithium manganese iron phosphate positive electrode material is 21-34m 2 / g; the average particle size range is 170-280nm.
12. A lithium manganese iron phosphate positive electrode material, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 11.
13. Use of the lithium iron manganese phosphate positive electrode material as claimed in claim 12 in positive electrode materials for lithium batteries.
Citation Information
Patent Citations
Composite lithium iron phosphate / carbon coated core-shell type lithium ferric manganese phosphate anode material and preparation method thereof
CN106340639A
Composite cathode material of lithium ion battery and preparation method thereof
CN107895781A
Composite material and preparation method thereof
CN111613786A
Method for producing carbon composite lithium manganese iron phosphate particle powder, carbon composite lithium manganese iron phosphate particle powder, and nonaqueous electrolyte secondary battery using carbon composite lithium manganese iron phosphate particle powder
WO2014034775A1